PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN, KEMISKINAN DAN KESEJAHTERAAN MASYARAKAT - I.B. Putu Purbadharmaja, Lisa Karlina Sitio, (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The economic growth of Riau Province experienced fluctuations from 2013-2017, this will affect the level of unemployment and poverty so it has an impact on people's welfare. The purpose of this study is to analyze the effect of economic growth on unemployment, poverty and social welfare. This study uses secondary data with 60 observations. Data collection was obtained by collecting data from BPS Riau. This study uses path analysis techniques, with the results of the study showing that economic growth is not a significant negative direct effect on unemployment and unemployment, not intervening variables of economic growth variables on community welfare, economic growth is not significantly positive effect directly on poverty and poverty is not an intervening variable of the variable economic growth on people's welfare, economic growth directly has a significant positive effect on people's welfare, unemployment directly has anpositive and significant effect on people's welfare, poverty directly has a significant negative effect on people's welfare.